Characterization And In Vitro Study Of Protoporphyrin Ix (Haem) Aptamer In Reversing Drug-Resistant Malaria - Abdulwahab, Aliyu (2024)
The global health challenge of malaria, compounded by drug resistance, necessitates innovative approaches for effective treatment. Aptamer technology is a promising tool towards combatting drug-resistant malaria especially chloroquine (cq) resistance. Preliminary study on protoporphyrin ix (haem) dna-aptamers (oka_24 and oka_26 ) demonstrated an anti-malarial property but lack the ability to internalise into the parasite-infected red blood cell (rbc). This research investigates the potential of cholesterol-tri ethylene glycol (col-teg) modified haem aptamers in addressing drug-resistant malaria. The research employs a multifaceted approach, including in silico techniques for predicting aptamer structures and molecular docking studies to assess binding behaviour. Additionally, reverse-phase high-performance liquid-chromatography (rp-hplc) was utilized to evaluate serum stability, while uv-absorption spectral titration and square wave voltammetry (swv) provided insights into the specificity and affinity of modified aptamers for haem. Cellular internalization assays, conducted using fluorescence-microscopy and flow cytometry, determine the efficiency of col-teg-modified aptamers in entering red blood cells. The study also examines the antimalarial activity of modified aptamers against cq-sensitive (3d7-strain) and cq-resistant (w2-strain) plasmodium falciparum. Docking analysis reveals that the transformation of oka_26 to col-teg-oka_26 does not alter binding behaviour,